Nephritic syndrome complicating placental site trophoblastic tumour: a case report and review of the literature - Satija, Tanya; Singh, Anju; Khurana, Sachin; Subbiah, Arunkumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Placental site trophoblastic tumour (PSTT) is rarely associated with renal disorders and has been described only a few case reports so far. Authors report the case of a 27-year-old female who presented with abnormal uterine bleeding post vaginal delivery and developed nephritic syndrome, thereafter. Detailed evaluation revealed increased levels of human chorionic gonadotropin (beta subunit)-β-hCG, and imaging findings suggesting gestational trophoblastic disease. The patient underwent hysterectomy, which led to immediate remission of proteinuria, ascites and hypertension. Thus, the diagnosis was confirmed as PSTT and, following treatment, her β-hCG became normal and proteinuria gradually disappeared. This type of association of gestational trophoblastic disease with renal disorders is a rare entity. A thorough review of the literature was also performed by us, in order to explain the pathophysiology as well as the relation between these conditions so that these unusual findings can be interpreted appropriately to achieve the correct diagnosis.